Pengaruh Pemeriksaan Pajak, Jumlah Wajib Pajak Dan Inflasi Terhadap Penerimaan Pajak Penghasilan (Studi Pada Kantor Pelayanan Pajak (KPP) Pratama Cibitung Periode 2017 – 2021) - Chika Alifia Monica; Tri Kunawangsih (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to investigate the effects of inflation, the number of taxpayers, and a tax audit on income tax receipts. The factors utilized in this study are Duty Review, Number of Citizens and Expansion as Autonomous Factors and Annual Expense Receipts as Reliant Factors. All Individual and Corporate Income Tax Receipts, registered Individual and Entity Taxpayers, the number of SKPKBs issued at KPP Pratama Cibitung, and the amount of inflation published monthly by the Central Bureau of Statistics (BPS) of Bekasi Regency in 2017, 2018, 2019, 2020, and 2021 (time series data of 60 months) comprise the population of this study. The saturated sampling method was used for the study's sample, which included the entire population. This sort of exploration utilizes illustrative examination which expects to make sense of the easygoing connection between the factors that impact speculation testing. Using the SPSS version 23 program, multiple regression analysis was used as the analytical method. According to the findings of this study, the Variable of Tax Audit has an effect on Income Tax Receipts, the Variable of Number of Taxpayers has an effect on Income Tax Receipts, and the Variable of Inflation has an effect on Income Tax Receipts.